IMPLEMENTASI MODEL EXPERIENTIAL LEARNING DALAM PEMBELAJARAN MENULIS TEKS BERITA SISWA KELAS VII SMP NUR AZIZI TANJUNG MORAWA - Carol Shelila Manik; Muhammad Oky Fardian Gafari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of the Experiential Learning model in teaching news text writing for seventh-grade students at SMP Nur Azizi Tanjung Morawa. This study employed a descriptive qualitative method. Research data were collected through observation, interviews, and documentation. The research subjects consisted of an Indonesian language teacher and VII-B students at SMP Nur Azizi Tanjung Morawa, while the research object was the implementation of the Experiential Learning model in teaching news text writing. The data were analyzed using Miles and Huberman's data analysis techniques, including data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the Experiential Learning model in news writing was carried out through the stages of lesson planning and lesson implementation. The lesson planning was developed through a teaching module containing learning components, including learning outcomes, learning objectives, learning materials, learning models, learning media, learning resources, and learning procedures. The implementation of learning was carried out in accordance with David Kolb's theory, namely opening activities, core activities consisting of concrete experience, reflective observation, abstract conceptualization, and active experimentation, as well as closing activities. The implementation of the Experiential Learning model provides students with opportunities to gain direct learning experiences, develop their understanding and apply it in news text activities, thus making the learning process more contextual and meaningful. It is expected that the findings of this study will be useful for educators, students, and future researchers who intend to implement the Experiential Learning model in teaching news text writing.